Diagnosis dan Tatalaksana Sindrom Marfan - Andi Mahavira; Bambang B Siswanto (The Indonesian Heart Association, 2013)
Background: Marfan syndrome is an autosomal dominant disorder of connective tissue, involving cardiovascular, ocular, skeletal and skin, pulmonary, and dura mater. Marfan syndrome is caused by mutations in the FBN1 gene on chromosome 15q21 encoding fibrillin-1, a glycoprotein in the extracellular matrix. Prevalence is 2–3 per 10 000, and 25–30% are new mutations. Morbidity and mortality mostly caused by dilation of the aortic root. Surgical therapy for aortic aneurysm can reduce life-threatening complication and also increase survival rate of Marfan syndrome. It is necessary to diagnose earlier and give appropriate medical therapy for optimal management of Marfan syndrome.Objective: to present a rare case, Marfan syndrome, viewed from diagnosis and management.Summary: A 32 year old woman diagnosed as severe AR was referred to NCCHK from Malang, East Java. According to several examination in clinic, this patient was diagnosed as severe AR on Marfan syndrome. Early diagnosis in Marfan syndrome will make better outcome. Bentall operation was done to this patient with a good result. Appropriate and continuous medical therapy are needed in post Bentall operation on Marfan syndrome patient.